Intervención en el Hogar Geriátrico San Vicente de Paúl en Barrios Altos - Sánchez Grados, Claudia Alejandra (2016)
Over all these years, Lima has been a city aspiring modernization, but the city may not forget it houses an important historic burden. Since 1991, and after several efforts, Lima´s Historic Center entered the list of World Heritage Sites recognized by UNESCO. Such recognition was achieved thanks to the Board of Lima founded in 1989 by a group of architects, artists, historians, and art critics who started different actions in order to rescue of our historic center. However, the question many people are asking is: On the one hand, what are we doing to protect and respect that title? And, on the other hand, do people know that this Historic Center includes other districts besides the well-known Lima Cercado?